Boğazköy, Türkei. Die kaiserzeitlichen Strukturen in der nördlichen Unterstadt von Boğazköy. Erste Ergebnisse der Arbeiten von 2019 bis 2021 - Krüger, Dominique (e-Forschungsberichte des DAI, 2022)
Since 2014, the excavations in Boğazköy-Ḫattuša have concentrated on the Northern Lower City. Parallel to the widespread remains from the Bronze Age and numerous burials, which indicate the extension of the known necropolis to the north, building structures from the Roman imperial period were identified for the first time. A military camp, built in the 1st century AD, was rebuilt several times until the 4th century AD. And, in the course of the last three campaigns, a structure that was initially interpreted as a villa rustica turned out to be a bath complex in connection with a large water basin. The decoration of the construction phase in the 2nd century AD corresponds to Roman urban models, which were, however, implemented in inferior quality by local craftsmen.